2020
DOI: 10.5194/esd-2019-94
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biases in the albedo sensitivity to deforestation in CMIP5 models and their impacts on the associated historical Radiative Forcing

Abstract: Abstract. Climate model biases in the representation of albedo variations between land cover types contribute to uncertainties on the climate impact of land cover changes since pre-industrial times, and especially on the associated Radiative Forcing. The recent publications of new observation-based datasets offer opportunities to investigate these biases and their impact on historical albedo changes in simulations from the fifth phase of the Coupled Model Intercomparison Project (CMIP5). Conducting such an ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…This experiment was partly motivated by a large land use forcing of −0.4 W m −2 in the CMIP5 HadGEM2-ES model (Andrews et al, 2017), which showed a large change in regional dust loading that contributed to this forcing. Our multi-model mean ERF of −0.09 W m −2 (−0.12 W m −2 if NorESM2-LM is excluded) agrees well with an observational-constrained analysis from CMIP5 models of −0.11 W m −2 (Lejeune et al, 2020) and is within the likely range of the AR5 assessment of −0.15 (−0.05 to −0.25) W m −2 .…”
Section: Land Use Changesupporting
confidence: 85%
“…This experiment was partly motivated by a large land use forcing of −0.4 W m −2 in the CMIP5 HadGEM2-ES model (Andrews et al, 2017), which showed a large change in regional dust loading that contributed to this forcing. Our multi-model mean ERF of −0.09 W m −2 (−0.12 W m −2 if NorESM2-LM is excluded) agrees well with an observational-constrained analysis from CMIP5 models of −0.11 W m −2 (Lejeune et al, 2020) and is within the likely range of the AR5 assessment of −0.15 (−0.05 to −0.25) W m −2 .…”
Section: Land Use Changesupporting
confidence: 85%
“…In particular, historical deforestation since the pre-industrial era has led to an increase in surface albedo corresponding to a global radiative forcing of −0.15 ± 0.10 W m −2 (Myhre et al, 2013). There are however large uncertainties, even concerning the sign of the effect, regarding the impacts of LCC on near-surface temperature due to persistent model disagreement (Davin et al, 2020;de Noblet-Ducoudré et al, 2012;Lejeune et al, 2017;Pitman et al, 2009). These disagreements arise from uncertainties in (1) the interplay between radiative (albedo) and non-radiative processes (surface roughness and evaporative fraction), (2) the role of local versus large-scale processes and feedbacks (Winckler et al, 2017), and (3) the magnitude of change in given surface properties (e.g.…”
Section: Albedo Changes Associated With Land Cover Transitionsmentioning
confidence: 99%
“…Overall, prior researched have focused on quantifying changes in carbon processes [7,22,27,41], or the short-term albedo change caused by snow melting or anthropogenic intervention like deforestation, afforestation, expansion of urban and cropland [18][19][20][21][22][23]. Our study reveals that the global land surface albedo has been steadily rising due to the long-term changes of vegetation and surface moisture.…”
Section: Discussionmentioning
confidence: 86%
“…In general, changes in surface albedo are associated with LULC conversions, LULC non-conversions and snow/ice melting. Previous research has mainly evaluated how changes in specific LULC types or type-to-type conversions caused by human activities have affected albedo and the associated radiative forcing [18][19][20][21][22][23]. These studies, failing to explore the influences of all possible LULC conversions and snow dynamics on surface albedo, can only provide a partial quantification of the effective changes in surface albedo.…”
Section: Introductionmentioning
confidence: 99%